Correlation of the location of superficial Barrett’s esophageal adenocarcinoma (s-BEA) with the direction of gastroesophageal reflux - Omae, Masami; Fujisaki, Junko; Shimizu, Tomoki; Horiuchi, Yusuke; Ishiyama, Akiyoshi; Yoshio, Toshiyuki; Hirasawa, Toshiaki; Yamamoto, Yorimasa; Tsuchida, Tomohiro; Igarashi, Masahiro; Seto, Yasuyuki (Endoscopy International Open, 2016)
Background: Superficial Barrett’s esophageal adenocarcinoma (s-BEA) in Barrett’s esophagus frequently occurs in the right wall of the esophagus. Our aim was to examine the correlation between the location of s-BEA and the direction of acid and non-acid reflux in patients with Barrett’s esophagus.Patients and methods: We performed 24-h pH monitoring in 33 s-BEA patients using a pH catheter with eight sensors. One sensor was located at the 6 o’clock position in the lower esophagus and sensors 1 – 8 were arranged counterclockwise at the same level. The catheter was positioned at the same level as the s-BEA. We measured the maximal total duration of acid (MTD-A) and non-acid (MTD-NA) reflux. When the direction of MTD-A and MTD-NA coincided with the location of the s-BEA, the case was defined as coincidental and we calculated the rate of coincidence, and the probability of the rate of coincidence was estimated with 95 % confidence intervals (95 %CI).Results: Among the 33 cases of s-BEA examined, the rate of coincidence of both MTD-A and MTD-NA was 24/33 (72.7 %) (95 %CI 0.54 – 0.87). The rate of coincidence of either MTD-A or MTD-NA was 30/33 (90.9 %) (95 %CI 0.76 – 0.98). Conclusions: Our study revealed that the location of s-BEA mostly corresponds to the direction of MTD-A or MTD-NA. Accurate observation of the distribution of acid or non-acid reflux by pH monitoring would aid early detection of s-BEA by endoscopy.